Reparative cardiac surgery in infants and small children: Five years experience with profound hypothermia and circulatory arrest. - Bender, H W (1979)
A five year experience of profound hypothermia and circulatory arrest in the operative management of severe congenital heart disease in 128 infants and children weighing 10 kg or less is reviewed. Hospital mortality was 13% for the entire series--8% in the last two years. Mortality varied with the defect present rather than with the age at operation, and appeared to decline over the five years. There was no morbidity associated particularly with this technique, and no evidence of permanent neurologic nor intellectual impairment. Total arrest time averaged 55 minutes, was related significantly to the defect being repaired, but was not related to hospital mortality. The results support the idea of definitive early cardiac repair for severely symptomatic infants and young children, rather than surgical palliation. The hypothermic arrest technique is attractive since it allows optimal operating conditions, thus permitting an accurate repair and the consequent improvement in surgical results.